PERENCANAAN PEMBELAJARAN: TUJUAN/INDIKATOR, PERANGKAT AJAR, DAN ASESMEN SEBAGAI BAGIAN DARI KOMPETENSI GURU - Amanda Ika Nurjanah; Fahmi; Adinda Aghni Soliha; Lirya Dovelima Azzahra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning planning is the primary foundation for quality educational processes. Competent teachers are required to design measurable learning objectives and indicators, develop innovative teaching materials, and implement comprehensive assessments. This study aims to develop an integrated learning planning model that integrates objectives/indicators, teaching tools, and assessment as a unified teacher competency framework within the Independent Curriculum (Kurikulum Merdeka) context. The method used is Research and Development (RnD) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) through literature study, needs analysis, product development, expert validation, and field testing. The results show that: (1) teachers' ability to formulate learning objectives aligned with Learning Achievement (CP) still requires strengthening; (2) development of innovative teaching modules has been proven to improve the quality of the learning process; and (3) integrated implementation of diagnostic, formative, and summative assessments significantly contributes to improving student learning outcomes. The developed model obtained 87.5% validity from experts and 82.3% effectiveness in field tests. The conclusion affirms that learning planning encompassing objectives/indicators, teaching materials, and assessment constitutes inseparable pillars of teachers' pedagogical competence in achieving meaningful learning.